Evaluation of some rodenticides and traps for controlling the Norway rat, Rattus norvegicus Berk., in poultry farms at Giza governorate, Egypt - Ahmed, M. M.; Wahba, A. A.; Al-Gendy, A. A.R.; Saber, E. M.M. (Journal of Phytopathology and Disease Management, 2017)
Different control methods (i.e. Zinc Phosphide 2% and 3%; Super Caid 0.005% and Live traps) against Rattus norvegicus Berk., evaluated by food consumption method in poultry farm (Bortos village -El Warraq area) at Giza Governorate during August and September 2016. The highest poison baits daily consumption were recorded when used Super Caid 0.005% (52.53 and 40.39 g/night) followed by Zinc phosphide 2% (0.23 and 1.93 g/night) and Zinc phosphide 3% (0.09 and 0.26 g/night) ) inside and outside building. The Super Caid 0.005% treatment gave high mortality numbers against R. norvegicus inside and outside the building. The pest mortality records increased from 3rd day until 6th day of treatment. Mortality records during treatment (inside building) were 7, 6, 6, 4 and 2 individuals in 7, 6, 5, 3 and 4 days, respectively. While mortality records during treatment (outside building) were 11 and 8 individuals in 6 and 7 days, respectively. The highest reduction of R. norvegicus when used Super Caid 0.005% were 79.98 and 46.04 % followed by Zinc phosphide 2% (51.85 and 36.51 %) and Zinc phosphide 3% (67.6 and 32.15 %) ) inside and outside building. While, when used live trap bait items inside building with attractants such as: tomato, lanshon, cucumber and falfel the reduction percentages in rat individuals were 78.41, 61.32, 92.43 and -65.1%, respectively. The analysis of variance and treatment means were significantly different between plain bait daily consumption pre-treatment of all transactions (Super Caid 0.005%, Zinc phosphide 2% and 3% inside and outside building and also live trap bait items).